Polyhydroxyalkanoate (PHA) Biosynthesis From Local Mixed Cultures And Burkholderia - Chee, Jiun Yee (2009)
Polyhydroxyalkanoate (PHA) production was conducted by mixed cultures obtained from various niches (rubber plantation soil, oil palm plantation soil, industrial aeration tank, industrial sedimentation tank, oil polluted wastewater and lake water) in Northern Peninsular Malaysia. Penghasilan polihidroksialkanoat (PHA) telah dikendalikan dengan menggunakan kultur campuran yang diperolehi dari pelbagai nic (tanah ladang getah, tanah ladang kelapa sawit, tangki pengudaraan industri, tangki pengenapan industri, air buangan yang dicemari minyak serta air kolam) di Utara Semenanjung Malaysia.